Vocational education and training in the age of digitalization : challenges and opportunities - Wuttke, Eveline [Herausgeber]; Seifried, Jürgen [Herausgeber]; Niegemann, Helmut [Herausgeber] (Barbara Budrich, 2020)
"The increasing digitalization of the world of work is associated with accelerated structural changes. These are connected with changed qualification profiles and thus new challenges for vocational education and training. Companies, vocational schools and other educational institutions must respond appropriately. On the one hand, digitalization offers many possibilities, especially with regard to the design of learning situations: Learning can be organized independently of time and place, so that training and continuing education processes can be flexibly and individually designed. On the other hand, it is becoming apparent that not all groups of learners benefit from digitalization and that the use of digital offers depends on variables such as the socio-economic background and educational status of learners. The use of digital media for learning processes can be supported different measures e.g. in vocational schools, which in turn presupposes that media-supported teaching is of high quality and that teachers know how to use media to support learning processes. The volume focuses on the diverse demands placed on teachers, learners and educational institutions in vocational education and training and aims to provide up-to-date results on learning in the digital age." (Publisher)
Keywords: G 2.2.1 Technologisierung; P 3.2.3 Lehrer; L 4.2.3 Internetbasiertes Lernen / E-Learning; Berufsbildung; Digitalisierung; Digitalkompetenz; Kompetenzentwicklung; Lernspiel; Berufsschullehrer; MOOC (Massive Open Online Courses)